Self-Esteem, Self-Monitoring, and Temperamental Traits in Action: Who Is Involved in Humanitarian, Political, and Religious Non-profit Organizations? - Kanafa-Chmielewska, Dorota (Frontiers in Psychology, 2021)
Self-esteem, self-monitoring, and temperamental traits are important factors that influence human behavior. The purpose of the present study was to compare groups involved in humanitarian (n = 61), political (n = 68), and religious (n = 54) activities in terms of intergroup differences in self-esteem, self-monitoring, and temperamental traits. There are two research questions that we sought to address: “What are the relationships between self-esteem, self-monitoring, and temperamental traits among those involved in social, religious, and humanitarian aid activities?” and “Do temperamental traits affect self-esteem and self-monitoring among volunteers?” The study was conducted in Poland among adults aged 18 years and older, during meetings of six selected nonprofit organizations, consisting of two organizations each in the humanitarian, political, and religious areas. The study used the Polish versions of the Rosenberg Self-esteem Scale, Snyders’ Self-Monitoring Scale, and the EAS Temperament Questionnaire. Volunteers of humanitarian organizations had the lowest self-esteem among all the examined groups. Politicians turned out to be more pragmatic than those involved in religious activities and humanitarian aid. Between the three examined groups, there were statistically significant differences in temperamental activity; the most active are those politically involved, followed by those involved in humanitarian aid and religious activities. Moreover, those involved in humanitarian aid reported a higher level of temperamental fear than those involved in political and religious activities. Furthermore, there were group differences in their reasons for social involvement. We discuss the potential sources of differences and consequences of outcomes for human resource practice in nonprofit organizations.